Formulation and phytochemical analysis of a potentially functional beverage from combining a leaf extract and pulp of Annona muricata (Annonaceae) - Nolasco-González, Yolanda; García-Magaña, María de Lourdes; León-Fernández, Andrés Eloy; Monribot-Villanueva, Juan L.; Guerrero-Analco, José A.; Montalvo González, Efigenia (Instituto de Ecología, A.C., 2023)
Background and Aims: Annona muricata beverages are widely used in traditional medicine to treat different ailments; however, they have been little characterized phytochemically and are consumed as sugary beverages, and may contribute to non-communicable diseases, including obesity. The objective of this work was to obtain and characterize a sensorially acceptable beverage from an extract of A. muricata leaves and pulp. Methods: A mixture design was used to formulate nine beverages by combining different ratios of the aqueous extract of A. muricata leaves and pulp. These beverages were subjected to physicochemical and sensory evaluation. Based on these results, one beverage was selected to be characterized by spectrophotometry and compared with an infused and commercial beverage. In addition, the selected beverage was further analyzed for its phytochemical composition by ultra-high-performance chromatography coupled to mass spectrometry and high-performance liquid chromatography coupled to a photodiode array detector. Key results: The selected beverage was formulated with 25% pulp, 50% leaf extract, and 25% water; it also displayed a 7.63 °Brix, pH 3.42, and 0.40% acidity. This beverage was up to three times higher in bioactive compounds than infused and commercial beverages. Fourteen phenolic compounds and two acetogenins were quantified, while two alkaloids (coclaurine and reticuline) and fifteen acetogenins were tentatively identified. Conclusions: The combination of A. muricata leaf extract and pulp is a vital alternative to obtain a sensorially acceptable beverage that contains bioactive compounds with a potential medicinal action since the phenolic compounds, alkaloids, and acetogenins present in the beverage could have efficient biological activities in the prevention of chronic degenerative diseases.